Factors Affecting Indonesia’s Import Duty Revenue - Syahni, Putri Purnama (Efficient: Indonesian Journal of Development Economics, 2021)
Import duty revenue is a source of government funds that can be used to finance development activities in an effort to create public welfare and grow a good progress of Indonesia’s economic activities. This study aims to analyze the factors that influence import duty revenue in Indonesia in the years 1989-2019. The analysis method used is multiple regression with the Error Correction Model (ECM) approach with time series data from 1989-2019. The results showed that the exchange rate of the IDR against the USD, the value of imports, and the index of economic openess had a significant effect on the acceptance of import duties revenue. This study suggests the government to be able to control the exchange rate of the IDR against the USD, tighten supervision related to procedures for import activities and be assessed not to make import duty revenue one of the main sources of state revenue. Penerimaan bea masuk merupakan salah satu sumber dana pemerintah yang dapat digunakan untuk membiayai kegiatan pembangunan dalam upaya menciptakan kesejahteraan masyarakat dan kelancaran dalam kegiatan perekonomian Indonesia. Penelitian ini bertujuan untuk menganalisis factor-faktor yang mempengaruhi penerimaan bea masuk di Indonesia pada tahun 1989-2019. Metode analisis yang digunakan adalah regresi berganda dengan pendekatan Error Correction Model (ECM) dengan data time series dari tahun 1989-2019. Hasil penelitian menunjukkan bahwa kurs rupiah terhadap dollar AS, nilai impor, dan indeks keterbukaan ekonomi berpengaruh signifikan terhadap penerimaan bea masuk. Sementara volume impor tidak berpengaruh terhadap penerimaan bea masuk. Penelitian ini menyarankan pemerintah agar mampu mengendalikan nilai tukar rupiah terhadap dollar AS, memperketat pengawasan terkait prosedur kegiatan impor dan dinilai untuk tidak lagi menjadikan penerimaan bea masuk sebagai salah satu sumber utama dalam penerimaan negara.